Nonfunctional Supernumerary Testis in a 26-Year-Old Man with Orchalgia - Christopher M. Simons; Moshe Wald (The Scientific World Journal)
Polyorchidism is a rare phenomenon, with 47 histologically confirmed cases and 77 total reported cases. In most patients, it is an incidental finding or an asymptomatic scrotal mass. More than half of histologically confirmed supernumerary testes have been reported to have the potential for sperm production. We report a case of a man with symptomatic left scrotal pain who was found to have a nonfunctional supernumerary testis in his left hemiscrotum.